2020
DOI: 10.1088/1751-8121/abae3f
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of vector solitons in a system of inhomogeneous coherently coupled nonlinear Schrödinger models with variable nonlinearities

Abstract: We investigate non-autonomous solitons in a general coherently coupled nonlinear Schrödinger (CC-NLS) system with temporally modulated nonlinearities and with an external harmonic oscillator potential. This general CCNLS system encompasses three distinct types of CCNLS equations that describe the dynamics of beam propagation in an inhomogeneous Kerr-like nonlinear optical medium for different choices of nonlinear polarizations owing to the anisotropy of the medium. We identify a generalized similarity transfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 67 publications
(162 reference statements)
0
10
0
Order By: Relevance
“…As a future study, the present investigation shall be extended to general solitons and their collisions with appropriate modulated nonlinearities which is reported recently [38]. Further, one can also study the dynamics of various nonlinear coherent structures, their co-existence and dynamics in dispersion as well as nonlinearity management in various systems, for example [39,40], by incorporating gain/ loss too.…”
Section: Importance Of the Similarity Parametersmentioning
confidence: 89%
“…As a future study, the present investigation shall be extended to general solitons and their collisions with appropriate modulated nonlinearities which is reported recently [38]. Further, one can also study the dynamics of various nonlinear coherent structures, their co-existence and dynamics in dispersion as well as nonlinearity management in various systems, for example [39,40], by incorporating gain/ loss too.…”
Section: Importance Of the Similarity Parametersmentioning
confidence: 89%
“…However, we can find only a handful amount of works for such variable background nonlinear waves compared to their counterparts on constant backgrounds. In the context of nonlinear optics, the effects of spatially-and temporally-varying backgrounds on solitons, breathers and rogue waves have revealed interesting outcomes that can be useful to understand the influence of nonuniform models [5,46,47]. Similarly, the dynamics of nonlinear waves on controllable backgrounds due to non-autonomous nonlinearities are explored in Bose-Einstein condensates too [6,[48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…The above studies revealed different exciting results such as amplification, compression, bending/snaking, tunnelling/cross-over, superposed structures, etc. [5,6,[46][47][48][49][50][51][52][53][54][55][56][57][58]. So, it is our natural interest to question the possibility of realizing such phenomena in the above mentioned fifth-order nonlinear model (1).…”
Section: Introductionmentioning
confidence: 99%
“…Hirota bilinear method is a direct and effective method for solving integrable nonlinear PDEs [27][28][29]. The Hirota bilinear method constructs the bilinear form of the original equation by introducing appropriate rational transformations to the potential function of the PDE.…”
Section: Introductionmentioning
confidence: 99%